Mothers Coping With Bereavement in the 2008 China Earthquake: A Dual Process Model Analysis. (November 2019) - Chen, Lin; Fu, Fang; Sha, Wei; Chan, Cecilia L. W.; Chow, Amy Y. M.
The purpose of this study is to explore the grief experiences of mothers after they lost their children in the 2008 China earthquake. Informed by the dual process model, this study conducted in-depth interviews to explore how six bereaved mothers coped with such grief over a 2-year period. Right after the earthquake, these mothers suffered from intensive grief. They primarily coped with loss-oriented stressors. As time passed, these mothers began to focus on restoration-oriented stressors to face changes in life. This coping trajectory was a dynamic and integral process, which bereaved mothers oscillated between loss- and restoration-oriented stressors. This study offers insight in extending the existing empirical evidence of the dual process model.